Guide for Didactic Communication in a Virtual Learning Environment - Lizárraga Halanocca, Gricelda (2024)
Every pedagogical practice is, in essence, a communication process. Under this premise, the goal of this research is to characterize didactic strategies framed within SEAD (Socioemotional and academic development) to achieve communication oriented to strengthening the bond with students within a virtual learning environment. The five-stage experience systematization method was applied to reconstruct the innovation proposal applied in a virtual freshman course at a particularuniversity. From this, the meaning of the experience was made explicit to infer communicable learning and transform knowledge. Results suggest that gamification strategies, effective communication, as well as socioemotional skills derived from character strengths, promote a wellbeing-based atmosphere which boosts learning. The role of teachers as agents which makeinteraction and communication in the virtual classroom dynamic is also highlighted.